Glomerular C4d Deposition and Kidney Disease Progression in IgA Nephropathy: A Systematic Review and Meta-analysisPlain-Language Summary - Yuanyuan Jiang; Jincan Zan; Sufang Shi; Wanyin Hou; Wenjing Zhao; Xuhui Zhong; Xujie Zhou; Jicheng Lv; Hong Zhang (Kidney Medicine, 2021)
Background: Glomerular deposition of C4d is a widely used biomarker for activation of the lectin pathway in the complement system and is reported to be associated with kidney progression in immunoglobulin A nephropathy (IgAN). The aim of this study was to evaluate whether glomerular C4d deposition, as a new biomarker, improves the prediction of kidney prognosis in IgAN. Study Design: Systematic review and meta-analysis. Setting & Population: Patients with biopsy-proven primary IgAN without age limitations.Selection Criteria for Studies: Cross-sectional or cohort studies reporting the prevalence of glomerular C4d deposition or evaluating its association with IgAN progression. Predictor: Glomerular C4d deposition. Outcome: Composite progression event of a >30% decline in estimated glomerular filtration rate or end-stage kidney disease. Results: 12 studies with 1,251 patients were included. The prevalence of glomerular C4d deposition was 34% (95% CI, 27%-41%), with large heterogeneity (I2 = 86%; P < 0.001). Patients with C4d deposition had lower estimated glomerular filtration rates (mean difference [MD], −11.48; 95% CI, −18.27 to −4.70; P < 0.001) as well as higher urinary protein-creatinine ratios (MD, 0.87; 95% CI, 0.53-1.21; P < 0.001) or 24-hour urinary protein excretion (MD, 0.99; 95% CI, 0.50-1.47; P < 0.001) and higher risk for hypertension (relative risk [RR], 1.45; 95% CI, 1.06-1.99; P = 0.02) than patients without C4d deposition. Glomerular C4d deposition was associated with a high Oxford classification score, including M1, E1, S1, and T1/2 lesions (all P ≤ 0.006). Patients with C4d deposition had higher rates of use of renin-angiotensin system blockers and immunosuppressants. Glomerular C4d was found to be a risk factor for the composite kidney event (RR, 3.17; 95% CI, 2.29-4.40; P < 0.001; adjusted HR, 2.05; 95% CI, 1.53-2.76; P < 0.001) and end-stage kidney disease (RR, 4.37; 95% CI, 3.15-6.07; P < 0.001) without evidence of heterogeneity. Limitations: The definition of positive C4d was not uniform and not all studies provided data about kidney outcomes. Conclusions: Glomerular C4d deposition is associated with an adverse prognosis and may be a useful biomarker of disease prediction in IgAN.